The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1136/lupus-2019-000339
|View full text |Cite
|
Sign up to set email alerts
|

Varicella zoster virus infections increase the risk of disease flares in patients with SLE: a matched cohort study

Abstract: ObjectiveTo explore whether varicella zoster virus (VZV) infection could increase the risk of disease flares in patients with SLE.MethodsPatients who had VZV reactivations between January 2013 and April 2018 were included from the SLE database (n=1901) of Shanghai Ren Ji Hospital, South Campus. Matched patients with SLE were selected as background controls with a 3:1 ratio. Patients with SLE with symptomatic bacterial infections of the lower urinary tract (UTI) were identified as infection controls. Baseline p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…38,39 In patients with SLE, viral infections can also trigger SLE flares after the virus is cleared. 39,40 In comparison, Influenza A infection in lupus-prone Fas lpr mice is cleared effectively and is not associated with worsening autoimmune features in the acute setting, although these mice can subsequently develop severe pulmonary inflammation weeks after viral clearance. 41 Notably, annual vaccination against influenza is associated with decreased hospitalization and ICU admissions in patients with SLE; hence this practice is highly encouraged.…”
Section: Relationship Between Sle and Risk Of Viral Infectionsmentioning
confidence: 99%
“…38,39 In patients with SLE, viral infections can also trigger SLE flares after the virus is cleared. 39,40 In comparison, Influenza A infection in lupus-prone Fas lpr mice is cleared effectively and is not associated with worsening autoimmune features in the acute setting, although these mice can subsequently develop severe pulmonary inflammation weeks after viral clearance. 41 Notably, annual vaccination against influenza is associated with decreased hospitalization and ICU admissions in patients with SLE; hence this practice is highly encouraged.…”
Section: Relationship Between Sle and Risk Of Viral Infectionsmentioning
confidence: 99%
“…A recent report described a disseminated VZV infection likely to have caused the death of a 49-year-old LN patient 29 . A matched cohort study confirmed that adult patients with SLE presented an increased risk of disease flares if they were infected with VZV 30 . Most of the reports of an effect of VZV on SLE/LN patients concerned adult patients with herpes zoster 30 , 31 .…”
Section: Discussionmentioning
confidence: 84%
“…A matched cohort study confirmed that adult patients with SLE presented an increased risk of disease flares if they were infected with VZV 30 . Most of the reports of an effect of VZV on SLE/LN patients concerned adult patients with herpes zoster 30 , 31 . To our knowledge, any effect of varicella disease on lupus remains to be reported.…”
Section: Discussionmentioning
confidence: 84%
“…A recent report described a disseminated VZV infection likely to have caused the death of an LN patient 28 . A matched cohort study con rmed that patients with SLE presented an increased risk of disease ares if they were infected with VZV 29 . To our knowledge, the young patient showed only mild symptoms limited to skin rash.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the young age (10) of the patient might be the reason why she suffered a mild disease despite her immune de ciency. Most of the reports of an effect of VZV on SLE/LN patients concerned older patients with herpes zoster 29,30 .The patient was diagnosed with SLE and LN at the age of 9 and was treated orally with 5mg glucocorticoid daily. After suffering from varicella, she was prescribed with proprietary Chinese medicine, Siji Antiviral Oral Liquid, Lysine Inosite and Vitamin B12 Oral Solution and treated with Acyclovir for external use.…”
Section: Discussionmentioning
confidence: 99%